Evaluation of multistress tolerant maize varieties for sustainable intensification in northern Guinea Savanna of north eastern Nigeria - Dugje, I.Y.; Odo, P.; Teli, I.A.; Asiedu, E.A. (2014)
Maize productivity is limited by multiple stresses in the savannas of West and Central Africa. Field trials were conducted in northern Guinea savanna of Nigeria in 2011 and 2012 to evaluate the performance of multi-stress tolerant maize varieties. Thirteen varieties including Local Check replicated three times were tested in randomized complete block design. Plant and ear heights were significantly higher for LNTP x LNP-WC3 and 2004 TZE-W DTSTRC4 than POOL 18-SR, 2009 TZE-W POP-STR, EVDT 99-W STR; and EVDT 2000-Y STRQPM, respectively. Striga count was significantly lower for EVDT 99-W STR and LNTP x LNP-WC3 than all the other entries. Days to 50% tassel and 50% silk were each significantly earlier for EVDT 99STR W-STR QPM, DT-W STR SYN, EVDT-99W STR and 2009 TZEW DT STR than the Local Check. Anthesis Silk Interval (ASI) was significantly lower for TZE COMP3 DT-WC2, 2009 TZEW DT STR, and EVDT 99-W STR than Local Check. Number of ears plant-1 was significantly higher for 2008 DTMA-Y STR than Local Check. Grain yield ha-1 was significantly superior for DT-Y STR SYN, 2008 DTMA-Y STR, 2004 TZE-W DTSTR C4, 2009 TZEW DT STR and EVDT 99-W STRQPM, respectively. Plant height was positively correlated with ASI and ear height, while ear height was positively associated with ears plant-1, days to 50% silk and 50% tassel. Grain yield ha-1 was positively correlated with ears plant-1, days to 50 % silk, days to 50% tassel and ear height, while ears plant-1 was negatively correlated with ear weight. Farmer selection criteria for acceptance of variety were in the order: Striga tolerance > nutrient value > drought tolerance > flour value > good taste > high yield > early maturity. The five varieties: DTY STR SYN, 2008 DTMA-Y STR, 2004 TZE-W DT STRC4, 2009 TZEW DT STR and EVDT 99-W STRQPM satisfied farmers criteria and were promising and thus nominated for on-farm demonstration and subsequent adoption in the region.